Banana waste and its circularity potential: a sustainable source of alternative foods, bioactive compounds, and food technological applications - Mohd Zaini, Nurul Solehah; Yaacob, Jamilah Syafawati; Gengatharan, Ashwini; Md Dahlal, Norazilawati; Azman, Ezzat Mohamad; Mohsin, Aliah Zannierah; Wan-Mohtar, Wan Abd Al Qadr Imad; Abd Rahim, Muhamad Hafiz (University of Sao Paolo, 2025)
Bananas rank among the most widely consumed fruits globally. However, their cultivation generates substantial waste, including peels, leaves, inflorescences, and pseudostems, with up to 80 % of the plant’s biomass being discarded. This waste not only poses considerable environmental and economic challenges but also represents an underutilized resource rich in unique nutritional and bioactive compounds, such as neurotransmitters, essential fatty acids, enzymes, and flavor constituents that are common in other agricultural byproducts. In this review, we present recent statistics on banana production and waste generation, alongside an examination of the potential applications of banana waste. These applications include direct consumption to combat malnutrition, incorporation into functional foods, the development of innovative food packaging, and contributions to sustainable agriculture. Additionally, we address the cultural significance of banana waste, review current life cycle analysis studies that highlight its environmental benefits, and outline the strategies for its valorization, addressing commercial viability, technical challenges, and regulatory considerations. By elucidating the processing challenges and multifunctional potential of banana waste in food science and technology, this study provides a comprehensive roadmap for leveraging this abundant resource to advance sustainable development goals, minimize agricultural waste, enhance global nutrition, and promote eco-friendly technological innovations.